Does Language Make a Difference? A Study of Language Dominance and Inhibitory Control - Salwei, Ashley Marie; de Diego-Lázaro, Beatriz (Frontiers in Psychology, 2021)
Although extensive research has been done to compare monolingual and bilingual children's executive function, there are fewer studies that look at the relation between bilingual children's languages and executive function. The purpose of this study was two-fold; first, to compare inhibitory control (executive function) in monolingual and bilingual children and second, to determine what vocabulary measure (dominant vs. non-dominant language) was related to inhibitory control in bilingual children. Twenty monolingual (English) and 20 bilingual (English-Spanish) children between the ages of 8 and 12 completed a vocabulary test (in English and Spanish) and an inhibitory control task (the flanker task). ANCOVAs revealed no significant differences between monolingual and bilingual children in reaction time or accuracy in the flanker task after controlling for maternal education. Partial correlations controlling for age showed that English expressive vocabulary (dominant language), but not Spanish, was positively correlated with inhibitory control (larger vocabulary, better inhibitory control), suggesting that bilingual children may use their dominant language to self-regulate over their non-dominant language, increasing the inhibitory control associated to the dominant language.